2020
DOI: 10.3389/fvets.2020.00387
|View full text |Cite
|
Sign up to set email alerts
|

Hemp in Veterinary Medicine: From Feed to Drug

Abstract: Hemp (Cannabis sativa) is an angiosperm plant belonging to the Cannabaceae family. Its cultivation dates back to centuries. It has always been cultivated due to the possibility of exploiting almost all the parts of the plant: paper, fabrics, ropes, bio-compounds with excellent insulating capacity, fuel, biodegradable plastic, antibacterial detergents, and food products, such as flour, oils, seeds, herbal teas, and beer, are indeed obtained from hemp. Hemp flowers have also always been used for their curative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 81 publications
0
28
0
1
Order By: Relevance
“…59 At present, to the best of our knowledge, no clinical studies regarding the use of cannabinoids in cats are available whereas there is a growing body of literature in dogs. 60 Nonetheless, considering cannabinoid properties, mechanisms of action and favourable results in treating other complex diseases of different species, it is believed that they could exert a positive therapeutic effect on some diseases that are still challenging for veterinarians, such as FCGS, by reducing the associated inflammation/pain and controlling dental plaque bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 At present, to the best of our knowledge, no clinical studies regarding the use of cannabinoids in cats are available whereas there is a growing body of literature in dogs. 60 Nonetheless, considering cannabinoid properties, mechanisms of action and favourable results in treating other complex diseases of different species, it is believed that they could exert a positive therapeutic effect on some diseases that are still challenging for veterinarians, such as FCGS, by reducing the associated inflammation/pain and controlling dental plaque bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…59 At present, to the best of our knowledge, no clinical studies regarding the use of cannabinoids in cats are available whereas there is a growing body of literature in dogs. 60…”
Section: Discussionmentioning
confidence: 99%
“…However, natural substances, such as polyphenols, that can interfere with phase I and/or II enzymes and/or with enteric P-glycoprotein enhance its plasma levels in rats ~6-fold ( 73 ). Finally, among the three compounds tested in our investigation, cannabidiol is the only ingredient that has been studied in dogs, where its detected oral bioavailability ranged from 13 to 19% of the administered dose ( 74 , 75 ). Therefore, despite our study being performed in vitro , these previously reported findings suggest that our results could be considered valid with respect to a nutraceutical approach to treating canine AD.…”
Section: Discussionmentioning
confidence: 99%
“…Hemp seed and hemp seed cake could be used as feed materials for all animal species and EFSA defined maximum incorporation rates in the complete feed per species e.g., 3–7% in poultry, 2–5% in pigs for hemp seed and hemp seed cake, 5% in ruminants for hemp seed cake and 5% in fish for hemp seed. Feeding efficacy trials also demonstrate that hemp and its derivates may be included in diets of livestock as a good source of crude protein and essential fats [ 61 , 62 ].…”
Section: Regulatory Framework In the Eu And North Americamentioning
confidence: 99%